Kuantan - Mars on Earth: Environmental Problems and Solutions - Mohd Yuhyi, Mohd Tadza (2016)
Over the past few months, bauxite mining has become a controversial environmental issue in Malaysia. Bauxite, a principle ore is a main source of aluminium. The presence of bauxite in Kuantan was first recognized almost eight decades ago in 1937. Kuantan’s bauxite is characterized as laterite bauxite by high ferric oxide content ranging from 14.4 to 40.6% depending on different deposits.